A Novel Neutrophil-Based Biomarker to Monitor Disease Activity and Predict Response to Infliximab Therapy in Patients With Ulcerative Colitis - Zhou, Zhou; Zhang, Yinghui; Pan, Yan; Yang, Xue; Li, Liangping; Gao, Caiping; He, Chong (Frontiers in Medicine, 2022)
Ulcerative colitis (UC) is characterized by refractory and recurrent mucosal inflammation, leading to a substantial healthcare burden. Diagnostic biomarkers predicting disease activity and treatment response remain elusive. Here, we evaluated the application value of a novel neutrophil-based index (the neutrophil-to-albumin ratio, NAR) as a novel diagnostic biomarker in patients with UC and a predictive marker for disease activity and response to infliximab (IFX) therapy. We enrolled a total of 146 patients with UC and 133 healthy controls. Clinical characteristics and laboratory parameters of enrolled subjects were retrieved from the electronic medical record database of our hospital. Serum cytokine and fecal calprotectin levels were measured by enzyme-linked immunosorbent assay (ELISA). Mucosa expression levels of inflammatory agents were measured by quantitative RT-PCR (qRT-PCR). We found that NAR, which had not yet been explored in UC, was significantly increased in patients with UC compared to that in controls. NAR showed a positive association with the disease activity and inflammatory load in patients with UC. Peculiarly, pre-treatment NAR predicted postinduction serum IFX trough level and exhibited a significant ability to discriminate initial responders from primary non-responders to IFX induction therapy. Our study provides evidences to utilize NAR in the diagnosis, activity monitoring, and IFX response prediction in patients with UC.